Analisis Kesiapan Kerja Lulusan Sekolah Menengah Kejuruan: Studi Kasus Jurusan Instalasi Tenaga Listrik - Arius, Pegi; Hambali, Hambali (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
This study aims to describe the Job Readiness of Graduates of the Electrical Power Installation Engineering Department at SMK Negeri 1 West Sumatra. Job readiness is a comprehensive individual condition that encompasses physical, mental, and experiential aspects of life, as well as the willingness and ability to perform work or an activity. The research method employed in this study is a descriptive approach with a quantitative orientation. The variables studied are the job readiness of graduates of the Electrical Power Installation Engineering Department of SMK Negeri 1 West Sumatra. The research instrument used in this study was a questionnaire that was distributed to respondents directly, which had 1 variable and 6 indicators. Based on the results of statistical calculations, the graduate job readiness variable is in the classification score of 76.7% ready to work, 23.3% likely to continue their education, or become entrepreneurs. The results of this study can be concluded that the job readiness of graduates of the Electrical Power Installation Engineering Department of SMK Negeri 1 West Sumatra, some continue to college, some work according to their fields and some work (Placeholder1) (Placeholder2) which is not following their field of expertise, and some are looking for work.